Effect of Onchocerca Volvulus Chitinase on MUC5B Expression in Human Airway Epithelial Cells. Issue 1 (January 2013) - Song, Si-Youn; Seo, Young Jung; Kim, Yong-Woon; Park, So-Young; Bae, Chang Hoon; Kim, Yong-Dae
Background: Chitin is an essential structural component of the wall of fungal cells and is present in the exoskeleton of arthropods. It has been generally assumed that mammals lack the ability to produce chitinase proteins, the enzymes responsible for chitin degradation. However, recent studies have indicated that mammals produce chitinases and chitinase-like proteins, and chitinase plays a potential role in human asthma and allergic inflammation. In this study, the effect and brief signaling pathway of chitinase on MUC5B expression were investigated in human airway epithelial cells. Methods: In the mucin-producing human NCI-H292 airway epithelial cells and the primary cultures of normal nasal epithelial cells, the effect and signaling pathway of chitinase on MUC5B expression were investigated using the reverse transcriptase–polymerase chain reaction (RT-PCR), real-time PCR, enzyme immunoassay, and immunoblot analysis with several specific inhibitors and small interfering RNA (siRNA). Results: In the mucin-producing human NCI-H292 airway epithelial cells, chitinase increased MUC5B expression. Chitinase significantly activated the phosphorylation of p38 mitogen-activated protein kinase (MAPK) but not the phosphorylation of extracellular signa-l-related kinase (ERK) 1/2. The SB203580 (p38 MAPK inhibitor) significantly attenuated chitinase-induced MUC5B mRNA expression, but U0126 (ERK1/2 inhibitor) did not. Knockdown of p38 MAPK by p38 MAPK siRNA significantly blocked chitinase-induced MUC5B expression. In the primary cultures of normal nasal epithelial cells, chitinase significantly increased MUC5B gene expression and this was significantly attenuated after pretreatment with SB203580. Conclusion: These results suggest that chitinase induces MUC5B expression by activation of the p38 MAPK signaling pathway in human airway epithelial cells.